Teori Perkembangan Sosial Emosi Erikson dan Perkembangan Moral Kohlberg - Habsy, Bakhrudin All; Sufiandi, Adhelia Caroline; Baktiadi, Athallah Nadhif; Asmarani, Eka Meylana (TSAQOFAH, 2024)
In this study, the researcher is interested in understanding Erikson’s theory of social development and Kohlberg’s moral development. The purpose of this reshearcher is to explore the theories of Erikson’s social development and Kohlberg’s moral development. The researcher employs a qualitative approarch thtough a literature review in conducting the study. The objects of investigation in this research are Erikson’s theory of social and Kohlberg’s moral development. The result of this study suggest that the development of each individual represent a universally predetermined stage in every human life. The processes occurring in each stage, as outlined, significantly influence the matured “Epigenrtic Principle”.